EL ABENCERRAJE Y LA HERMOSA XARIFA Polimorfismo letterario e dinamiche testuali - D'Agostino, Alfonso (Biblioteca di Carte Romanze. Series minor, 2021)
A jewel of Renaissance short fiction, the progenitor of the Moorish tale and one of the greatest examples of literary "maurophilia", El Abencerraje y la hermosa Xarifa is a novella with an Italianate style, set on the fifteenth-century frontier between the Christian kingdoms and that of Granada: it tells a story of high moral content, tinged with stoicism and senechism: The young Moor Abindarráez, a member of the noble and unhappy Granada family of the Abencerrajes, goes to visit his beloved Xarifa to join her in marriage, but on the way he is captured by the famous castellan Rodrigo de Narváez, who, however, having heard his story, leaves him temporarily free to go and marry, binding him to the promise to return immediately afterwards to give himself up. From military virtue to moral virtue, a contest of generosity and loyalty cements the friendship between the Christian knight and the pair of noble Moors, showing the way to mutual recognition based on high human values. In the fifties and sixties of the sixteenth century this story was rewritten three times (by different authors), whose philological relations are extremely complex: the book discusses the main theories on this subject, proposing a new vision, hopefully less hypothetical than the others, of the interweaving of tradition and accompanies the study with a new edition, closer to the original mises en page, of all the sixteenth-century texts involved.